Depreciation Calculation Using the Straight Line Method is appropriate Taxation Law - Oktiyani*, Rina; Ela Revita, Maria Lapriska Dian; Sugiarti, Sugiarti (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The Income Tax Law in Indonesia regulates that costs incurred to acquire tangible assets, which have a useful life of more than one year, can be deducted from gross income through a depreciation mechanism. There are two (1) methods for depreciation of tangible assets referred to in the tax law. Straight-line method, (2). Declining balance method (declining balance method). The aim of this research is to find out (1) how to calculate depreciation based on tax regulations (2) how to calculate depreciation using the straight line method based on tax regulations. In this research the author used descriptive qualitative methods and literature study. Fixed assets (Assets) other than buildings, can be depreciated using the straight-line or declining balance method. Meanwhile, fixed assets (property) are in the form of buildings, depreciation can only be done using the straight line method. The research results show that the provisions for calculating depreciation of tangible assets made by companies need to be reconciled fiscally. Based on the Depreciation Cost Reconciliation calculation, the depreciation calculation uses the straight line method, there is a difference between Commercial calculations and Fiscal calculations in accordance with tax provisions.